Emotional Skills with Homogeneity Psycho Cognition Strategy: A Study of Physical Education in Elementary Schools - Albertus Fenanlampir; John Rafafy Batlolona; Siti Divinubun; Marleny Leasa (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
The emotional skills of elementary school students in physical education subjects are still minimal. Therefore, a deeper exploration in this study was conducted to uncover it. This study aims to analyze the relationship of emotional intelligence with homogeneity psycho cognition strategies in physical education students in elementary schools. This study aims to analyze the relationship between emotional skills and homogeneity psycho cognition strategies in the physical education of elementary school students. The results showed a relationship between emotional skills and homogeneity psycho cognition strategies in physical education subjects. Some factors cause the absence of a relationship between physical education and homogeneity psycho cognition strategies of elementary school students. The results showed a relationship between emotional skills and homogeneity psycho cognition supported by adequate collaboration and emotional by all students. Other factors are reduced or limited interaction between students and the learning environment, aggravated by an economic burden that causes parents' emotional problems that impact children's emotions. Therefore, homogeneity psycho cognition can be recommended in physical education learning to improve the emotional skills of elementary school students.